Blockchain beyond Bitcoin: Block Maturity Level Consensus Protocol - Memon, M. (Institute of Electrical and Electronics Engineers Inc., 2019)
This paper enlightens the stipulation of blockchain beyond the bitcoin and identifies the key challenges in the implementation of blockchain on a small scale or newly implemented projects based on the literature review, furthermore it also introduces Block maturity level (BML) as a Consensus protocol, which eliminates the 51 attack, the hardfork problem and small-scale problem by introducing sub-blocks as a defense mechanism against attackers. This technique can be used in the implementation of blockchain where the hash power and difficulty is lower and easy to match-up. This proposed consensus protocol would immensely secure the implementation of the blockchain on different projects. Â© 2018 IEEE.